HUBUNGAN STATUS GIZI DENGAN TINGKAT KESEGARAN JASMANI SISWA DI SD NEGERI 015 PASAR BARU PANGEAN KABUPATEN KUANTAN SINGINGI - Wadiun, Jufri; Saripin, Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT, based on observations of researchers at SDN 015 Pasar Baru Pangean Regency Kuantan Singingi, some students is low or not so well their physical fitness level. This is evident from the appearance and their attitude and conduct, especially in following penjasorkes learning materials, which impressed the students lazy to do sports activities, tired, lackluster and there is a pale face seemed less healthy. From the problems researchers speculate that because the nutritional status of the students, therefore the researchers conducted a study on the relationship with the nutritional status of students' physical fitness. This type of research is correlational while samples were students of class V SDN 015, amounting to 17 people with a total sampling technique. The data in this study were obtained from tests of nutritional status by measuring height and weight of students, TKJI existing test 5 test items. Data were analyzed using product moment correlation and using the Liliefors test for normality. Based on the analysis of data obtained rhiutng 0.310 <0.497 rtabel, in other words Ha Ho accepted and rejected that means it can be concluded that there is no relationship of nutritional status with physical fitness level students of SDN 015 Pasar BaruPangean Regency Kuantan Singingi.Keywords: Nutritional Status, Physical Freshness